2017
DOI: 10.1007/s00442-017-3815-6
|View full text |Cite
|
Sign up to set email alerts
|

Expanding our understanding of leaf functional syndromes in savanna systems: the role of plant growth form

Abstract: The assessment of leaf strategies has been a common theme in ecology, especially where multiple sources of environmental constraints (fire, seasonal drought, nutrient-poor soils) impose a strong selection pressure towards leaf functional diversity, leading to inevitable tradeoffs among leaf traits, and ultimately to niche segregation among coexisting species. As diversification on leaf functional strategies is dependent on integration at whole plant level, we hypothesized that regardless of phylogenetic relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 70 publications
1
22
0
2
Order By: Relevance
“…irradiance conditions (Rossatto & Franco 2017). Despite the fact that this pattern was clearly observed in the set of typical savanna species studied here, their values of SLA were higher and their tissue thicknesses were lower than those reported for typical non-arboreal savanna species in Central Brazil (see the study by Rossatto et al 2015).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…irradiance conditions (Rossatto & Franco 2017). Despite the fact that this pattern was clearly observed in the set of typical savanna species studied here, their values of SLA were higher and their tissue thicknesses were lower than those reported for typical non-arboreal savanna species in Central Brazil (see the study by Rossatto et al 2015).…”
Section: Discussionmentioning
confidence: 47%
“…Considering these results in the context of forest expansion over savannas (Stevens et al 2017) and the ecophysiology of non-arboreal savanna plants (Rossatto & Franco 2017), it can be postulated that the persistence of non-arboreal plants in encroached situations may occur only with the set of leaf anatomical strategies presented here by the FS plants. As the TS species showed thicker leaves, with anatomical traits that are advantageous to survive under elevated light irradiances (Rossatto et al 2015;Rossatto & Franco 2017), this may imply that they cannot thrive under shaded conditions, which in turn can explain why the diversity of such species drastically decrease from the TS to the FS (Pinheiro et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly the case for traits associated with carbon gain, considering morphological (specific leaf area) and physiological aspects (maximum photosynthesis and stomatal conductance) (Pérez-Harguindeguy et al 2013). Many studies reported how these traits enable plant persistence in savanna environments (Lemos Filho 2000;Prado et al 2004;Franco et al 2005;Habermann et al 2011;Souza et al 2015;Rossatto and Franco 2017); which are characterized by a series of selective pressures such as fire, rainfall seasonality, lower content of soil nutrients and elevated irradiance (Franco 2002). Such studies, however, focused only on tree species, a diverse, but not unique, component of the savanna ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The 'leaf' is one of the three organs of vascular seed plants, taxonomically classified under angiosperms. The remaining two, namely root and stem of a vascular plant, facilitate sprouting, support the function of a leaf to assimilate solar energy through photosynthesis and generate biochemical energy through respiration (Tanaka et al, 2015;de la Riva et al, 2016;Rossatto and Franco, 2017). Hence, leaves, although looking flexible, feeble, thin and vulnerable, provide innumerable cubic metre surface area in the canopy for the absorption of blue and red wavelengths from sunlight and therefore contribute to the enhancement of biomass (Tanaka et al, 2015).…”
Section: Introductionmentioning
confidence: 99%